A case report on hyperpigmentation in vitamin B12 deficiency - Verma, Vivek Kumar; Vijayavarman, V. (International Journal of Research in Medical Sciences, 2019)
Cobalamin (Vitamin B12) is a water-soluble vitamin. Cobalamin is synthesized only by microorganisms. The only source of vitamin B12 for humans is food of animal origin. Hyperpigmentation of skin has been reported only rarely as the presenting manifestation of vitamin B12 deficiency. We report a patient who had hyperpigmentation as her presenting medical complaint and in whom Vitamin B12 deficiency was the cause. A 36-year-old female presented with generalised weakness and progressive and asymptomatic hyperpigmentation of hand and feet for 5 months. She is vegetarian by diet. On examination, hyperpigmentation was present over dorsal aspect of metacarpophalangeal, proximal and distal interphalangeal joints. Hyperpigmentation were present over dorsum of the foot and over the joints. The tongue was depaillated, and hyperpigmentation was present. Her serum level of vitamin B12 was diminished (83pg/ml). Megaloblastic anemia presents with protean manifestations. The association between vitamin B12 deficiency and hyperpigmentation, although unusual, has been described. Cutaneous manifestations associated with B12 deficiency include characteristic mucocutaneous hyperpigmentation (most common), vitiligo, angular cheilitis, and hair-nail changes. It mainly affects knuckle pads and oral mucosa. It is an under-recognized sign of megaloblastic anemia and should always be looked for in the setting of pallor. Hyperpigmentation could be the earliest manifestation of vitamin B12 deficiency before anemia sets in. It is worthwhile to consider the possibility of vitamin B12 or folate deficiency in a patient with unexplained pigmentary changes. Early detection and adequate treatment will prevent anemia and various neurological manifestations.